Inquiry into leisure and recreation patterns and their relationship to open space and landscape design : the case of Jeddah, Saudi Arabia - Al-Shahrani, Mohammad Ali (The University of Edinburgh, 1992)
Urban open spaces in Jeddah as a recreational facility fail to respond to the people's desires and needs. Factors, such as culture and climate, that influence the people behaviour and their use of the environment and these facilities are ignored in planning and designing of these places. Alien planning and design concepts gave priority to vehicular movement and maximized the public domain. Community open spaces and gardens assumed to be the primary resource for recreation for the family members. They have the accessibility advantage for everyday recreational activities. This is more important if we take into consideration the fact that children, ladies, elders and disabled have no direct access to cars. However, these open spaces often inadequately designed, maintained and managed which resulted in underutilization of valuable assets. This research investigates the relationship between leisure and recreation pattern and the use of the recreational urban open spaces in the city of Jeddah. It shows the present situation of these facilities. The thesis starts by introducing the problem and discussing some of the factors that affect leisure and recreation, such as religion, time, privacy and climate. In order to pursue the origin of the problem, the thesis discusses the development of the recreational open spaces and facilities in three periods of the city history. These are referred to as traditional, transitional and modem. It shows how the social life, the urban pattern and the recreation and leisure patterns developed from the traditional environment to the modem. It manifests the change in the social life, the environment and the emergence of new recreational facilities. The research involved carrying out survey and observations of selected open spaces in Jeddah in the spring of 1989. The questionnaire investigates the people desires, needs and use of the existing recreational open spaces and facilities. The open space observations explore intensity of use, type of activities, type of users and their behaviour in using these open spaces. Then, implications of the results are discussed and the nature of the problem is defined. The research is concluded by explaining the approach to solve these problems.
Keywords: Parks; City planning; Jeddah